Avaliação das citocinas inflamatórias em ratos obesos-msg suplementados ou não com taurina - Caetano, Luiz Carlos (2013)
Among the several organic alterations arising from obesity, chronic inflammation is associated with the balance of cytokines TNF-α, IL-1β, IL-6, IL-2, IFNg, IL-4 and IL-10, and there is evidence the amino acid taurine (Tau) has anti-inflammatory effect. Therefore, this study investigated the inflammatory profile in plasma and retroperitoneal adipose tissue of MSG-obese rats, supplemented or not, with the TAU. Male Wistar rats received subcutaneous injections of MSG (4mg/kg body weight/day) or hyperosmotic saline during the first 5 days of life, composing the control (CON) and MSG groups. After 21 days, half of each group received TAU 2.5% in drinking water, and separated into 04 groups: CON, CON with TAU (CTAU), MSG and MSG with TAU (MTAU). At 120 days of age, the animals were euthanized. The MSG rats showed an increase in Lee Index, retroperitoneal and perigonadal fat pads deposition, insulin and triglycerides plasmatic concentrations and HOMA-IR, when compared to CON animals, showing that the treatment with MSG led to obesity. The TAU supplementation attenuated retroperitoneal fat deposition, as well as TG concentration. The MSG treatment did not alter the expression of JNK and IκBα. However, the supplementation with TAU increased 61% the expression of IkBα in CTAU group compared to the CON and 107% in the MTAU animals compared to the MSG. The expression of TNF-α, IL-1β and IL-6 in the retroperitoneal adipose tissue were similar in the four groups of animals, as well as plasma concentrations of TNF-α, IL-1β, IL-6, IL-2, IFNγ, IL-4 and IL-10. It is possible to conclude that neonatal treatment with MSG does not influence the inflammatory profile of the animals. We also conclude that the TAU increased 61% of IkBα protein expression in the control group and 107% in the MSG-obese animals, without affecting the inflammatory cytokines. Thus we suggest that TAU can exert their anti-inflammatory effects in adipose tissue, via NF-kB